Innovation: The Key Factor Of Competitiveness For Chinese SMES - Luo, Murong; Al-Shami, Samer Ali Hussein; Mansor, Nusaibah (Universidad del Zulia, 2019)
Purpose-This study aims to present an overview of SMEs’ innovation in China, to identify the main problems, and provide practical suggestions. Design/methodology/approach-The research of this paper is based on the collection and evaluation of existing literature and survey reports. Findings-This study presents the general situation and characteristics of SMEs’ innovation in China, and concludes the main reason that hinders Chinese SMEs’ innovation is the lack of human resources, capital, innovation culture and information. Practical implications-This study suggests that, in addition to improving resources and environment, SMEs can also try to adopt micro-innovation to promote innovation activities. These suggestions are practical and can help SMEs maintain competitiveness. Originality/ value-This study provides an overview of Chinese SMEs’ innovation, which can be the basis for future research in this area.